2022
DOI: 10.1063/5.0085137
|View full text |Cite
|
Sign up to set email alerts
|

From film to ring: Quasi-circular inorganic lead halide perovskite grain induced growth of uniform lead silicate glass ring structure

Abstract: Polycrystalline properties of perovskites can induce the growth of different nanostructures, thanks to their facile fabrication. In this work, the CsPb2Br5 perovskite grains were used as templates to induce the growth of the ring-like structures on a SiO2/Si substrate. Owing to the oxidation of the volatile PbBr2 originated from the decomposition of CsPb2Br5, the grain boundaries of perovskites are prone to reaction with SiO2, which leads to the formation of Pb-silicate glass at high temperatures. The quasi-ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…, CsBr and PbBr 2 ). 205 It has been reported that embedding CsPbBr 3 QDs into TeO 2 -based inorganic glass can lower the temperature (from 1100 °C to 630 °C). However, the water stability decreases to 120 hours correspondingly.…”
Section: Stabilization Methodsmentioning
confidence: 99%
“…, CsBr and PbBr 2 ). 205 It has been reported that embedding CsPbBr 3 QDs into TeO 2 -based inorganic glass can lower the temperature (from 1100 °C to 630 °C). However, the water stability decreases to 120 hours correspondingly.…”
Section: Stabilization Methodsmentioning
confidence: 99%